OPTIMASI PARAMETER PEMBUBUTAN PADA MATERIAL AISI 4340 MENGGUNAKAN METODE TAGUCHI DAN GREY RELATIONAL ANALYSIS - Otto Purnawarman; Achmad Sambas; Bella Rukmana (Jurnal Teknologi Terapan, 2024)
In the turning process, the parameters of cutting speed (Vc), feed rate (f), and nose radius (rε) are things that influence the quality of the product. This study aims to optimize the relationship between the parameters of tool wear and surface roughness. AISI 4340 low alloy steel workpiece material and carbide insert cutting tools are used. The method used is a statistical application approach with the Taguchi method, gray relational analysis (GRA) techniques to get the best level combination for multi-response results and Analysis of variance (ANOVA) to determine factors that affect tool wear and surface roughness. The factor used is cutting speed. (Vc), feed rate (f), and nose radius (rε) with three levels and the responses are surface roughness (Ra) and tool wear (VB). The results of the ANOVA show that cutting speed (Vc) and feed rate (f) are significant factors for surface roughness and tool wear. The optimal factor level values for obtaining surface roughness (Ra) and minimum tool wear (VB) were Vc level 1 = 73.73 m/min, f level 1 = 0.1 mm/rev, and rε level 1 = 1.2 mm.